PERAN PACAR BAGI EMERGING ADULTHOOD LAKI-LAKI: (Studi Deskriptif) - Felicia Wongso (Perpustakaan Universitas Surabaya, 2014)
The role of girlfriend is the one important thing when dating. The purpose of this research is to describe the role of girlfriend for men. The subjects were college students in University of Surabaya, aged 18 until 25 years, and never dating, in a relationship, or have not been dating. The result shows that there were six factors that contribute to the roles of girlfriend, such as future orientation, social support, the authority of work, sexual intimacy, proximity, and similarity. The emerging adulthood already execute the role as an adult by choose the path of his life according to their thinking, which is visible from the ability to choose a girlfriend. The role of girlfriend for men is being a matter of consideration for a prospective life partner. This research is expected to benefit the development of psychology, parents, and men about the description of girlfriend’s role for men as an emerging adulthood.